Participatory Evaluation of Resilient Potato Varieties in Climate-Smart Villages of Lushoto in Tanzania - Harahagazwe, D.; Quiróz, R.; Kuoko, Stephen; Recha, John W.M.; Radeny, Maren A.O.; Sayula, George; Schulte-Geldermann, Elmar; Brush, Gladness; Msoka, Elizabeth; Rimoy, Mary; Bonierbale, Merideth W.; Atakos, Vivian; et al. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
This three-year study conducted by the International Potato Centre (CIP) in collaboration with Selian Agricultural Research Institute (SARI) was based on demand by Lushoto farmers through the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). This participatory action research (PAR) was aimed at developing more resilient potato varieties that can grow in both long and short rainy seasons and give higher yields. The approach involved training-of-trainers (ToT) and participatory varietal selection (PVS) experiments. The ToT comprised five training events using modules. Three training events were done in the long rainy season and two in the subsequent short rainy season. The topics covered in the first round of training were on integrated crop management, from land preparation to seed storage. The second round of training was participant-driven whereby topics emerged from the first training. A total of twenty-one participants representing farmers, extension services and local non-governmental organizations were trained. The training was supported by field experiments using the CIP Mother and Baby Trials model. The trials were carried out in five villages: Kwesine, Boheloi, Maringo, Kwekitui and Milungui. Experimental materials comprised six advanced and heat tolerant clones from CIP (CIP390478.9, CIP388767.1, CIP392797.22, CIP300055.32, CIP398208.29 and CIP397073.7), two local varieties (Kidinya and Obama), an improved variety recently registered in Tanzania (Asante) and a popular farmer’s variety but registered in Kenya (Shangii). A cross-analysis of field and culinary data combining quantitative and qualitative assessments from the three seasons of field evaluations showed a certain consistency in the high yielding ability and acceptability of four genotypes, namely Asante, Shangii, CIP392797.22 and CIP398208.29. The two clones were then named by farmers and proposed for official release while Shangii was proposed for registration for commercial use.